Taxonomic review of tropical western Atlantic shallow water Drilliidae (Mollusca: Gastropoda: Conoidea) including descriptions of 100 new species - Fallon, Phillip J. Jr. (Zootaxa, 2016)
A review of the literature and examination of over 3,200 specimens of shallow water (<200 m) tropical western Atlantic (TWA) Drilliidae Olson, 1964 in museum and private collections has resulted in the recognition of numerous previously undescribed species, 100 of which are proposed here for the first time. A total of 65 names were found in the literature. Of these, 48 are considered valid, 16 synonyms, and one nomen dubium. In addition, characteristics that distinguish each genus currently in use for TWA shallow water species have indicated the need for reassignment (new combinations within Drilliidae) of 15 species. Some nomenclatural actions have come about from the literature review and include one taxon placed in junior synonymy (under an older name recently re-discovered) and one new name for a junior homonym. Two neotypes, five lectotype designations, and one new name are also proposed. Altogether, nomenclatural actions on 17% of valid previously described taxa are proposed. The 100 proposed names are placed in 12 available and one new genus: Agladrillia Woodring, 1928 (2), Bellaspira Conrad, 1868 (7), Calliclava McLean, 1971 (3), Cerodrillia Bartsch & Rehder, 1939 (11), Clathrodrillia Dall, 1918 (6), Decoradrillia, new genus (4), Douglassia Bartsch, 1934 (4), Fenimorea Bartsch, 1934 (15), Leptadrillia Woodring, 1928 (12), Lissodrillia Bartsch & Rehder, 1939 (8), Neodrillia Bartsch, 1943 (2), Splendrillia Hedley, 1922 (13), and Syntomodrillia Woodring, 1928 (13). These are the first reports of Calliclava in the western Atlantic, previously known only from the eastern Pacific. The new genus, Decoradrillia, is proposed to hold four new species and one existing that share a unique shell microsculpture and other morphological traits. One genus, Drillia Gray, 1838, is not currently believed to have TWA representatives. Three genera comprised exclusively of bathyal species are not treated in this work: Clavus Monfort, 1810 (=Eldridgea Bartsch, 1934), Globidrillia Woodring, 1928, and Spirotropis Sars, 1878. The significant increase in species within all of the genera has the effect of strengthening the groups’ diagnostic characters by their presence across a greater number of species. Each of the 148 valid species treated herein are described (or redescribed) and photographs of types presented, as are photographs of morphological variants and representatives from separate geographic areas, if available, to illustrate species’ variability.